Planning to stay in the countryside: The insider-advantages of young adults from farm families. (August 2020) - Stockdale, Aileen; Ferguson, Sara
Abstract: There is growing interest in immobility studies prompted by declining internal migration rates. While recent studies have examined the agency of stayers, this paper sheds light on an overlooked structural influence in a rural context: namely, planning policy on house building in the countryside. Using young adult interview data from a pilot study in rural Northern Ireland we demonstrate a strong place attachment with the home area which is entangled in complex patterns of family history, farm ownership and continuing familial networks. This attachment translates into an equally strong desire to stay, which is enabled through Northern Ireland's different past and present countryside planning policies. A planning presumption in favour of countryside development at specific times has facilitated one-off self-built homes by farm families. Such development is regarded as normal and represents the least expensive route into owner-occupied housing. However, the policy provides young adults from farm families with a considerable insider-advantage when it comes to being able to stay in the countryside and, as a consequence, staying may become the preserve of those from existing farm families. Highlights: Rural planning policy which permits one-off self build housing is an important structural factor in enabling young adults to stay in rural areas. Place attachment to rural places is entangled in complex webs of family history, farm ownership and familial networks. Rural planning policy is an important structural factor in enabling young adults to stay. Rural place attachment relates to family history, farm ownership and familial networks. Family farms help maintain a personal connection to previous generations.